Density Log Correlation with Coal Proximate in the Muaraenim Formation, Musi Banyuasin, South Sumatera - Khairani, Mutia; Amin, Sarwo Sucitra; Adithya, Bagus (Jurnal Bio-Geo Material Dan Energi, 2025)
This research is located in the PT BSPC area using the well logging method as the beginning of coal exploration activities. There are 7 well logging data with coal quality values in the form of moisture content, ash content and calorie data. From processing and interpretation using WellCAD 5.7 software, the lithology of the research area was obtained in the form of clay, coal, sandstone, carbonseous clay and coal. At 7 points, 9 coal seams were found, namely seams A11, A1, A, B11, B, B, C, D1 and D. The thickest seam is seam B with an average thickness of 5.85 m. From the correlation, the relationship of log density with proximate data had a fairly strong relationship except for the caloric value which had no correlation with the coal seam C in the study area. For the most influential correlation to the density value is the moisture content. The quality of seam B coal is better than seam C coal. On average, seam B has a calorie of 5531 cal/gr while seam C is lower at 5153 cal/gr. These two seams have a fairly high ash content, but seam B has a lower moisture content of 16.13% while seam C has a moisture content of 16.65%.